2015
DOI: 10.15386/cjmed-380
|View full text |Cite
|
Sign up to set email alerts
|

The apelin-APJ system in the evolution of heart failure

Abstract: Heart failure is a chronic, progressive disease in which the overexpression of biologically active molecules and neurohomonal activation are the key factors of the evolution and natural history. The apelin-APJ system is a newly discovered molecular pathway and the RAAS counterbalance is its principal effect. The apelin is a potent inotrope, vasodilator and diuretic with crucial cardioprotective effects against angiotensin and aldosterone injuries. Intense and prolonged RAAS induces the downregulation of the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…Apelin is also reported to suppress TGF‐β1‐induced epithelial‐mesenchymal transition and epithelial‐mesenchymal transition‐associated fibrogenic gene induction . Importantly, apelin is known to antagonize the renin‐angiotensin‐aldosterone system . Thus, Fc‐apelin‐13 may exert cardiac benefits by lessening cardiac fibrosis and improving energy metabolism in addition to the increase of cardiac output in obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apelin is also reported to suppress TGF‐β1‐induced epithelial‐mesenchymal transition and epithelial‐mesenchymal transition‐associated fibrogenic gene induction . Importantly, apelin is known to antagonize the renin‐angiotensin‐aldosterone system . Thus, Fc‐apelin‐13 may exert cardiac benefits by lessening cardiac fibrosis and improving energy metabolism in addition to the increase of cardiac output in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…50 Importantly, apelin is known to antagonize the renin-angiotensin-aldosterone system. 51 Thus, Fc-apelin-13 may exert cardiac benefits by lessening cardiac fibrosis and improving energy metabolism in addition to the increase of cardiac output in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…3 Exogenous apela can interact with APJ receptors in mammalian tissues and cells to exert corresponding biological effects. [4][5][6][7][8][9][10] Previous basic experiments have also shown that apelin can improve cardiac function in mice with myocardial infarction by inhibiting myocardial cell apoptosis, promoting angiogenesis and inhibiting myocardial fibrosis. 11 Sustained apela gene therapy can improve blood pressure in high-salt diet hypertension rats.…”
Section: Introductionmentioning
confidence: 99%
“…Apelin is widely expressed in the endothelium, binds to G protein-coupled receptor (APJ) in endothelial cells, myocardial cells, and smooth muscle cells and activates its following signalling pathways such as PI3K/Akt, activation of nitric oxide (NO) syntheses (eNOS), and NO production [14][15][16]. Apelin/APJ system (expression of apelin and APJ in the serum and myocardial tissue) has been downregulated in severe and uncompensated HF in experimental and clinical studies [17,18]. Low serum apelin levels following MI have also been documented in a clinical study in which the control was 38 patients with no prescribed medications, without history of cardiac events, and with a normal electrocardiogram and transthoracic echocardiography [19].…”
Section: Introductionmentioning
confidence: 99%